2018
DOI: 10.1155/2018/7067608
|View full text |Cite
|
Sign up to set email alerts
|

Static and Dynamic Properties and Temperature Sensitivity of Emulsified Asphalt Concrete

Abstract: Asphalt concrete is a typical rheological material, which is hard brittle at low temperature and reflects soft plastic facture at high temperature; the temperature has a great influence on the mechanical properties of asphalt concrete. In order to eliminate the environmental pollution caused by hot asphalt construction, cationic emulsified asphalt can be used. is paper transforms the temperature control system for static and dynamic triaxial test equipment, which has achieved static and dynamic properties of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…For most of the large public buildings and special industrial structures, the key parts are generally built using new-type structures made of steel and concrete [1][2][3][4][5][6][7][8][9]. Although concrete structures have good corrosion resistance and durability, they are a kind of non-combustible material, and their mechanical properties are quite sensitive to temperature [10][11][12][13][14][15][16]. Since concrete structure buildings are prone to fire disaster with fast temperature rise and heavy smoke accumulation, once the temperature exceeds the limit temperature of steel and concrete, the structure of the building will be broken, and the bearing capacity and safety performance of the rest parts will be irreversibly weakened, thereby making the overall structure of the building be easily damaged or even collapse in severe cases [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…For most of the large public buildings and special industrial structures, the key parts are generally built using new-type structures made of steel and concrete [1][2][3][4][5][6][7][8][9]. Although concrete structures have good corrosion resistance and durability, they are a kind of non-combustible material, and their mechanical properties are quite sensitive to temperature [10][11][12][13][14][15][16]. Since concrete structure buildings are prone to fire disaster with fast temperature rise and heavy smoke accumulation, once the temperature exceeds the limit temperature of steel and concrete, the structure of the building will be broken, and the bearing capacity and safety performance of the rest parts will be irreversibly weakened, thereby making the overall structure of the building be easily damaged or even collapse in severe cases [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…S. Pirmohammad et al [ 7 ] carried out three-point fracture tests and found that the fracture resistance of hydraulic asphalt concrete first increased and then below a certain temperature (−20 °C) decreased. Huang et al [ 8 ] suggested that following the addition of temperature, the initial tangent modulus and failure strain of hydraulic asphalt concrete increases significantly employing experiments on the temperature sensitivity of asphalt concrete. Studies investigating the mechanical properties of hydraulic asphalt concrete were carried out using uniaxial compression tests and triaxial compression tests by Wang [ 9 ] and Zhang [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ning [ 17 ] employed the hydraulic servo device to test the dynamic compressive features of hydraulic asphalt concrete at various temperatures and he reported that the failure modes of hydraulic asphalt concrete present distinct strain rate effect under various temperatures. Huang [ 8 ] analyzed the dynamic characteristics of asphalt concrete using a dynamic triaxial machine with an adjusted temperature control system. As the impermeable core in dams, hydraulic asphalt concrete has a relatively high bitumen content and excellent temperature sensitivity.…”
Section: Introductionmentioning
confidence: 99%